Evaluasi Sumber Daya Teknologi Informasi Perusahaan Menggunakan COBIT 5 (Studi Kasus: PT Krakatau Steel (Persero) Tbk) - Fadel Muhafiizh; Suprapto Suprapto; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
PT Krakatau Steel (Persero) Tbk is a limited liability company under the command of BUMN which is engaged as the largest integrated steel producer in Indonesia. Corporate information technology governance is an important part of ensuring that the availability of the information technology has supported the achievement of the company's business objectives. With the problems found on existing resources, human resource management, and knowledge management of employees, information technology resource management on PT Krakatau Steel (Persero) Tbk. The COBIT 5 framework is considered to be an appropriate framework for information technology resource management. This study focuses on the COBIT 5 subdomain EDM04: Ensure Resource Optimisation, APO07: Human Resources Optimisation, and BAI08: Manage Knowledge and to determine the current of capability level and GAP's value. The result of EDM04 value is 3 at level 3 and GAP 1, APO07 is 2.3 at level 2 and GAP 0.7, and BAI08 is 2.7 at level 2 and GAP 0.3. In creating the recommendations, use SWOT analysis. The recommendation is focusing on controlling each procedure, implementing redundancy in the regeneration of infrastructure, labor demand, and updating and improving the analysis results on the knowledge management website, and increasing employee competency.